2017
DOI: 10.1186/s13287-017-0579-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of human adipose tissue-derived stem cells on breast cancer cells: implications for cell-assisted lipotransfers in breast reconstruction

Abstract: BackgroundIn this study we evaluated the interactions of human adipose tissue-derived stem cells (ADSCs) and different human breast cancer cell lines (BRCAs) with regard to the safety of cell-assisted lipotransfers for breast reconstruction and a thereby unintended co-localization of ADSCs and BRCAs.MethodsADSCs were co-cultured with five different human BRCAs (MCF-7, MDA-MB-231, SK-BR-3, ZR-75-30, and EVSA-T) and primary BRCAs from one patient in a transwell system, and cell-cell-interactions were analyzed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 44 publications
1
50
0
Order By: Relevance
“…MMP8 mRNA expression is only detected in MDA-MB-231 cells [121,123,124], except in one study that found no expression [125]. Co-culture with adipose tissue-derived mesenchymal stem cells, a driver of tumorigenesis, did not affect the MMP8 expression of breast cancer cells [126]. Although MMP8 was mainly found to be expressed by metastatic cell lines and not the non-metastatic MCF-7 cell line, many [123,124,127] have shown that MMP8-expressing breast cancer cell lines are less invasive in vitro and generate less metastases in mice in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…MMP8 mRNA expression is only detected in MDA-MB-231 cells [121,123,124], except in one study that found no expression [125]. Co-culture with adipose tissue-derived mesenchymal stem cells, a driver of tumorigenesis, did not affect the MMP8 expression of breast cancer cells [126]. Although MMP8 was mainly found to be expressed by metastatic cell lines and not the non-metastatic MCF-7 cell line, many [123,124,127] have shown that MMP8-expressing breast cancer cell lines are less invasive in vitro and generate less metastases in mice in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have demonstrated that ASCs promote breast cancer cell migration, stemness and promote angiogenesis [30,31,32]. ObASCs have been shown to promote tumor growth and metastasis of MCF7 through increased secretion of leptin, which upregulates aromatase and ERα [24].…”
Section: Discussionmentioning
confidence: 99%
“…Specific regenerative properties of ASCs could be used in breast reconstructive surgery after a mastectomy has been performed. However, its utility in this condition is quite controversial and could raise concerns about their proliferative effect on residual tumor cells [139,140]. Direct myocardial injection of allogeneic ASCs has been found to be safe and has presented a tendency toward improvement in cardiac function in patients with ischemic heart disease and ischemic heart failure [141].…”
Section: Human Clinical Trialsmentioning
confidence: 99%